The Birth of the Eye Vesicle: When Fate Decision Equals Morphogenesis - Giger, Florence A.; Houart, Corinne (Frontiers in Neuroscience, 2018)
As the embryonic ectoderm is induced to form the neural plate, cells inside this epithelium acquire restricted identities that will dictate their behaviour and progressive differentiation. The first behaviour adopted by most neural plate cells is called neurulation, a morphogenetic movement shaping the neuroepithelium into a tube. One cell population is not adopting this movement: the eye field. Giving eye identity to a defined population inside the neural plate is therefore a key neural fate decision. While all other neural population undergo neurulation similarly, converging towards the midline, the eye field moves outwards, away from the rest of the forming neural tube, to form vesicles. Thus, while delay in acquisition of most other fates would not have significant morphogenetic consequences, defect in the establishment of the eye field would dramatically impact the formation of the eye. Yet, very little is understood of the molecular and cellular mechanisms driving them. Here, we summarise what is known across vertebrate species and propose a model highlighting what is required to form the essential vesicles that initiate the vertebrate eyes.